Battery active material adhesive and preparation method thereof
By developing a battery active material binder based on polyurethane, polyurea, epoxy resin or polyimide, the problems of traditional binders due to reduced raw material production and insufficient electrochemical performance are solved, and higher thermal stability and structural stability are achieved, extending the service life of the battery and reducing costs.
Patent Information
- Application Number
- CN202510083952.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The traditional lithium-ion battery binder polyvinylidene fluoride (PVDF) has caused battery structural damage and performance degradation due to the reduction in raw material production and insufficient electrochemical performance. The new fluorine-containing copolymer has high cost and limited performance improvement.
A battery active material binder is developed, using a combination of polymer homopolymer or copolymer, conductive agent and solvent. The main structure is polyurethane, polyurea, epoxy resin or polyimide. The reactive monomer and curing agent components are gradually polymerized in the solvent to form polymer chains, which enhances the adhesion force and reduces the dissolution of transition metals.
It improves the thermal stability and structural stability of the positive electrode composite material, extends the cycle stability and service life of the battery, reduces the risk of transition metal dissolution, and avoids the problem of high costs.
Smart Images

Figure CN119899622A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery binders, and in particular relates to a battery active material binder and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have a series of advantages such as high specific capacity, high operating voltage, good safety, and no memory effect. They are now widely used in 3C products such as smart phones, power and energy storage fields. With the expansion of the market scale, the continuous expansion of battery application fields and the continuous upgrading and replacement of corresponding products, higher and higher requirements are placed on lithium-ion batteries. Battery active materials are one of the key materials of lithium batteries and determine the main performance of lithium batteries. During the cycle of batteries such as ternary and lithium iron phosphate batteries, transition metals such as Ni, Co, Mn, and Fe in the skeleton of the positive electrode active material of the battery will dissolve into the electrolyte, causing the electrolyte to decompose, thereby causing the destruction of the overall structure of the battery. In addition, the traditional binder polyvinylidene fluoride (PVDF) is polymerized by 1,1-difluoroethylene (VDF), and the upstream raw material is R142b, which is in the phase-out period as a second-generation refrigerant. PVDF is easily dehydrogenated under the action of residual alkali to form double bonds, thereby forming a gel, losing its bonding properties and producing byproducts that are harmful to electrochemistry.
[0003] In order to hedge against the increase in PVDF prices caused by the future reduction in R142b production and to further improve the electrochemical properties of the binder, the development of new binders is particularly important. Most new binders are copolymers of VDF and fluorinated monomers such as tetrafluoroethylene, which are essentially modified PVDF. While the performance is slightly improved, the cost is greatly increased. Among the new positive electrode active material binders, only a small amount of polyacrylonitrile and polyacrylate have been reported. Summary of the invention
[0004] The purpose of the present invention is to provide a battery active material binder and a preparation method thereof in order to solve the above problems, thereby solving the problems mentioned in the background technology.
[0005] In order to solve the above problems, the present invention provides a technical solution:
[0006] A battery active material binder, comprising a high molecular homopolymer or copolymer, a conductive agent and a solvent;
[0007] The mass percentage of the polymer homopolymer or copolymer in the solvent is 1%-20%, and the main structure of the polymer homopolymer or copolymer is one of polyurethane, polyurea, epoxy resin or polyimide;
[0008] The solvent is at least one of NMP (N-methylpyrrolidone), DMAc (N,N-dimethylacetamide), DMF (N,N-dimethylformamide), DAA (diacetone alcohol) and THF (tetrahydrofuran).
[0009] Preferably, the mass percentage of the conductive agent in the solid content of the slurry is 1%-10%, and the conductive agent is at least one of Super P Li (conductive carbon black), conductive graphite and carbon nanotubes.
[0010] A method for preparing a polyurethane or polyurea binder comprises the following steps:
[0011] A1. Mix diisocyanate, monoanhydride, diamine, diol, monoamine, monoalcohol and solvent;
[0012] A2, mixing at a temperature of 20-40°C for 1-3 hours;
[0013] A3, a chain polyurethane or polyurea material mixed at a temperature of 60-120°C for 6-10 hours, with a solid content concentration of 1%-20%;
[0014] The diisocyanate structural formula is
[0015] The general structural formula of the diamine is
[0016] The general structural formula of the monoamine is R3-NH2 ;
[0017] The general structural formula of the monoalcohol is R 4 -OH .
[0018] Preferably, the molar ratio of the sum of the monoamine and monoalcohol to the sum of the diamine, diol and diisocyanate is 2:n:(n+1), wherein n is 2-1000.
[0019] A method for preparing an epoxy resin adhesive comprises the following steps:
[0020] B1, mixing diglycidyl ether, monoglycidyl ether, diamine, dicarboxylic acid and solvent;
[0021] B2, mixing at a temperature of 20-40°C for 1-3 hours;
[0022] B3, a chain epoxy resin material having a solid content concentration of 1% to 20% and mixed at a temperature of 60 to 120°C for 6 to 10 hours;
[0023] The diglycidyl ether structural formula is
[0024] The general structural formula of the diamine is
[0025] The general structural formula of the monoglycidyl ether is
[0026] The general structural formula of the dicarboxylic acid is
[0027] Preferably, the molar ratio of the monoglycidyl ether and diglycidyl ether to the diamine or dicarboxylic acid is 2:n:(n+1), wherein n is 2-1000.
[0028] A method for preparing a polyimide adhesive comprises the following steps:
[0029] C1, mixing tetracarboxylic dianhydride, monoanhydride, diamine and solvent;
[0030] C2, mixing at a temperature of 20-40°C for 1-3 hours;
[0031] C3, a chain polyimide material having a solid content concentration of 1% to 20% and mixed at a temperature of 60 to 150°C for 6 to 10 hours;
[0032] The general structural formula of the tetracarboxylic dianhydride is
[0033] The general structural formula of the diamine is
[0034] Preferably, the molar ratio of the monoanhydride to the tetracarboxylic dianhydride and the diamine is 2:n:(n+1), wherein n is 2-1000;
[0035] The monoacid anhydride is at least one selected from phthalic anhydride, hexahydrophthalic anhydride, maleic anhydride, tetrahydrophthalic anhydride, pentanedetracarboxylic dianhydride, methylmaleic anhydride and itaconic anhydride.
[0036] A positive electrode sheet, comprising a current collector and a positive electrode active layer, wherein the positive electrode active layer contains a battery active material or a binder prepared by any of the above methods;
[0037] The current collector is at least one of copper foil, aluminum foil, composite copper foil and composite aluminum foil;
[0038] The battery active material is a positive electrode active material, and the battery active material is at least one of lithium cobalt oxide, nickel-cobalt binary battery active material, nickel-manganese binary battery active material, nickel-cobalt-manganese ternary battery active material, lithium-rich battery active material and lithium iron phosphate;
[0039] The positive electrode sheet prepared with the above-mentioned binder effectively improves the thermal stability and structural stability of the positive electrode composite material, thereby improving the electrochemical properties of the positive electrode composite material, such as cycle stability and service life.
[0040] A secondary battery comprises the positive electrode sheet mentioned above.
[0041] The beneficial effects of the present invention are as follows: the adhesives recorded in the present application are non-fluorinated polyurethanes, epoxy resins, and polyimide polymers, all of which are gradually polymerized in a solvent with monomers such as diisocyanates, diglycidyl ethers, and tetracarboxylic dianhydrides having high reaction activity and corresponding diamines, diols, diacids, etc. as curing agent components to form polymer chains. Compared with PVDF, groups such as N and O with lone pair electrons interact with transition metals, thereby increasing the adhesion and reducing the dissolution of transition metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] For ease of explanation, the present invention is described in detail with reference to the following specific implementations and the accompanying drawings.
[0043] Figure 1 It is a schematic flow chart of a method for preparing a binder, a positive electrode slurry, a positive electrode sheet, and a secondary battery provided in an embodiment of the present application;
[0044] Figure 2 is a schematic diagram of the synthesis of the polyurethane material provided in Example 1 of the present application;
[0045] Figure 3 is a schematic diagram of the synthesis of the polyurea material provided in Example 2 of the present application;
[0046] Figure 4 is a schematic diagram of the synthesis of the epoxy resin material provided in Example 3 of the present application;
[0047] Figure 5 is a schematic diagram of the synthesis of the polyimide material provided in Example 4 of the present application;
[0048] Figure 6 It is a cycle stability test curve chart of the secondary batteries provided in Examples 1-4 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0049] like Figure 1-6 As shown, the specific implementation adopts the following technical solutions:
[0050] The positive electrode active material is selected from: at least one of lithium cobalt oxide, nickel-cobalt NC binary battery active material, nickel-manganese NM binary battery active material, nickel-cobalt-manganese NCM ternary battery active material, lithium-rich battery active material, and lithium iron phosphate; these positive electrode active materials have a higher compaction density, which is beneficial to make secondary batteries such as lithium carriers have higher capacity performance and energy density.
[0051] The steps of preparing chain polyurethane, polyurea, epoxy resin and polyimide materials include: preparing a difunctional monomer (diisocyanate, diglycidyl ether, tetracarboxylic dianhydride), a difunctional curing agent (diamine, diol), and a monofunctional monomer or curing agent into a solution with a mass fraction of 5-20%; mixing components that do not react chemically with each other, recording the monomer as liquid A and the curing agent as liquid B, slowly dropping liquid B into liquid A at a certain temperature, stirring continuously, adding a solvent to dilute if the viscosity is too high, and continuing to stir until the reaction converges after the dropwise addition is completed; if the final product is polyimide, the polyamic acid in this stage needs to be stirred for 6-10 hours at a temperature of 100-150°C, and high-temperature thermal imidization dehydration ring closure is performed to generate polyimide.
[0052] The molar ratio of the monofunctional monomer, the difunctional monomer and the difunctional curing agent or (the monofunctional curing agent, the difunctional curing agent and the difunctional monomer) is 2:n:(n+1), wherein n is 2-100; wherein the monofunctional monomer or the curing agent plays the role of regulating the molecular weight and end-capping to avoid residual active groups in the final adhesive.
[0053] The solvent is selected from at least one of NMP, DMAc, DMF, DAA and THF; these solvents have good solubility for all monomers and curing agents and provide a suitable solvent environment for the polymerization reaction.
[0054] The second aspect of the present application provides a method for preparing a positive electrode plate, which comprises mixing a binder solution, a battery active material, and a conductive agent, adding a small amount of solvent if necessary, and fully dispersing them with a planetary mixer to obtain a slurry to be coated.
[0055] Example 1
[0056] Preparation of a battery active material binder:
[0057] At room temperature, HDI (hexamethylene diisocyanate) was dissolved in NMP to prepare an isocyanate solution with a solid content of 20 wt% and a dibutyltin dilaurate catalyst of 0.1 mol% of the total reactants was added. 1,6-hexanediol and 1-butanol were dissolved in NMP to prepare a 20 wt% alcohol solution. The alcohol solution was slowly added to the isocyanate solution at a molar ratio of 1-butanol: 1,6-hexanediol: HDI = 2:99:100, and NMP was gradually added to dilute the final solution to 5 wt%. After stirring at room temperature for 1 hour, stirring at 60°C for 8 hours, a 5 wt% NMP solution of polyurethane PHHO was obtained, i.e., a binder solution.
[0058] Preparation of a positive electrode sheet:
[0059] 1. Mix the binder PHHO, battery active material, Super P Li conductive agent and NMP evenly, transfer to a planetary mixer and stir and mix at a revolution speed of 7200 rpm for 12 minutes to obtain a positive electrode slurry with a solid content of 40%; wherein the weight ratio of battery active material: binder: Super P Li is 93:2:5;
[0060] 2. Use a flat-plate coating machine to coat the slurry on dry aluminum foil with a coating density of 3-20 mg / cm2, then blow dry at 70°C until there is no obvious liquid. After rolling, transfer the electrode to a vacuum oven and vacuum dry at 100°C overnight to obtain the positive electrode.
[0061] A secondary battery is provided, wherein positive electrode sheets are assembled into 2025 button-type batteries in an argon atmosphere glove box, and the negative electrode is a lithium sheet.
[0062] Example 2
[0063] Preparation of a battery active material binder:
[0064] At room temperature, HDI (hexamethylene diisocyanate) was dissolved in NMP to prepare an isocyanate solution with a solid content of 20 wt%, 1,6-hexanediamine and 1-hexylamine were dissolved in NMP to prepare a 20 wt% amine solution, and the amine solution was slowly added to the isocyanate solution at a molar ratio of 1-hexylamine: 1,6-hexanediamine: HDI = 2:99:100, and NMP was gradually added to dilute the final solution to 5 wt%. After stirring at 45°C for 1 hour, stirring at 60°C for 8 hours, a 5 wt% NMP solution of polyurea PHHN was obtained, i.e., a binder solution.
[0065] Preparation of a positive electrode sheet:
[0066] 1. Mix the binder PHHN, battery active material, Super P Li conductive agent and NMP evenly, transfer to a planetary mixer and stir and mix at a revolution speed of 7200 rpm for 12 minutes to obtain a positive electrode slurry with a solid content of 40%; wherein the weight ratio of battery active material: binder: Super P Li is 93:2:5;
[0067] 2. Use a flat-plate coating machine to coat the slurry on dry aluminum foil with a coating density of 3-20 mg / cm2, then blow dry at 70°C until there is no obvious liquid. After rolling, transfer the electrode to a vacuum oven and vacuum dry at 100°C overnight to obtain the positive electrode.
[0068] A secondary battery is provided, wherein positive electrode sheets are assembled into 2025 button-type batteries in an argon atmosphere glove box, and the negative electrode is a lithium sheet.
[0069] Example 3
[0070] Preparation of a battery active material binder:
[0071] At room temperature, HDE (1,6-hexanediol diglycidyl ether) and C8-C10 alkyl glycidyl ether were dissolved in NMP to prepare an epoxy solution with a solid content of 20wt%, 1,6-hexanediamine was dissolved in NMP to prepare a 20wt% amine solution, and the epoxy solution was slowly added to the amine solution at a molar ratio of alkyl glycidyl ether: HDO: 1,6-hexanediamine = 2:99:100, and NMP was gradually added to dilute the final solution to 5wt%. After stirring at 45°C for 1 hour, stirring at 60°C for 8 hours, a 5wt% NMP solution of polyurea PHHE was obtained, i.e., a binder solution.
[0072] Preparation of a positive electrode sheet:
[0073] 1. Mix the binder PHHE, battery active material, Super P Li conductive agent and NMP evenly, transfer to a planetary mixer and stir and mix at a revolution speed of 7200 rpm for 12 minutes to obtain a positive electrode slurry with a solid content of 40%; wherein the weight ratio of battery active material: binder: Super P Li is 93:2:5;
[0074] 2. Use a flat-plate coating machine to coat the slurry on dry aluminum foil with a coating density of 3-20 mg / cm2, then blow dry at 70°C until there is no obvious liquid. After rolling, transfer the electrode to a vacuum oven and vacuum dry at 100°C overnight to obtain the positive electrode.
[0075] A secondary battery is provided, wherein positive electrode sheets are assembled into 2025 button-type batteries in an argon atmosphere glove box, and the negative electrode is a lithium sheet.
[0076] Example 4
[0077] Preparation of a battery active material binder:
[0078] At room temperature, MCDA (5-(2,5-dioxotetrahydrofuranyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride) and succinic anhydride were dissolved in NMP to prepare an anhydride solution with a solid content of 20wt%, and 1,6-hexanediamine was dissolved in NMP to prepare a 20wt% amine solution. The anhydride solution was slowly added to the amine solution at a molar ratio of succinic anhydride: MCDA: 1,6-hexanediamine = 2:99:100, and NMP was gradually added to dilute the final solution to 5wt%. After stirring at room temperature for 1 hour, stirring at 120°C for 10 hours, a 5wt% NMP solution of polyimide PMH, i.e., a binder solution, was obtained.
[0079] Preparation of a positive electrode sheet:
[0080] 1. Mix the binder PMH, battery active material, Super P Li conductive agent and NMP evenly, transfer to a planetary mixer and stir and mix at a revolution speed of 7200 rpm for 12 minutes to obtain a positive electrode slurry with a solid content of 40%; wherein the weight ratio of battery active material: binder: Super P Li is 93:2:5;
[0081] 2. Use a flat-plate coating machine to coat the slurry on dry aluminum foil with a coating density of 3-20 mg / cm2, then blow dry at 70°C until there is no obvious liquid. After rolling, transfer the electrode to a vacuum oven and vacuum dry at 100°C overnight to obtain the positive electrode.
[0082] A secondary battery is provided, wherein positive electrode sheets are assembled into 2025 button-type batteries in an argon atmosphere glove box, and the negative electrode is a lithium sheet.
[0083] Comparative Example 1
[0084] Preparation of a positive electrode sheet:
[0085] 1. Mix the binder PVDF, battery active material, Super P Li conductive agent and NMP evenly, transfer to a planetary mixer and stir and mix at a revolution speed of 7200 rpm for 12 minutes to obtain a positive electrode slurry with a solid content of 40%; wherein the weight ratio of battery active material: binder: Super P Li is 93:2:5;
[0086] 2. Use a flat-plate coating machine to coat the slurry on dry aluminum foil with a coating density of 3-20 mg / cm2, then blow dry at 70°C until there is no obvious liquid. After rolling, transfer the electrode to a vacuum oven and vacuum dry at 100°C overnight to obtain the positive electrode.
[0087] A secondary battery is provided, wherein positive electrode sheets are assembled into 2025 button-type batteries in an argon atmosphere glove box, and the negative electrode is a lithium sheet.
[0088] Peel force test
[0089] The electrode sheet resistance and peeling force of the electrode sheets prepared in Examples 1-4 and Comparative Example 1 were tested with a coating density of 20 mg / cm2 and a 3M tape for peeling force. The test results are shown in (Table 1). Regardless of whether the adhesive is polyurethane, polyurea, epoxy resin or polyimide, the electrode sheet resistance is at a similar level and can meet the requirements of the battery. Therefore, it can be concluded that these novel adhesives can form a good dispersion of the battery active material and the conductive agent.
[0090] Since polyurethane, polyurea, and epoxy resin contain groups similar to metal ligands such as -NCN-, -NCO-, and -NCCOCCO-, they can form coordination effects with the metals in the battery active materials and current collectors, and the peeling force on the electrode is higher than that of relatively rigid polyimide and PVDF without coordination groups.
[0091] Table 1. Summary of electrode resistance and peeling force test
[0092] Volume resistivity (Ω·cm) Interface resistance (Ω·cm2) Peel force (N / cm) Example 1 1.33 17.5 18.7 Example 2 1.35 19.1 17.1 Example 3 1.54 20.4 19.5 Example 4 1.36 17.0 15.6 Comparative Example 1 1.41 18.8 12.1
[0093] Further, in order to verify the progress of the embodiments of the present invention, the button cells prepared in embodiments 1-4 and comparative example 1 were subjected to cycle stability tests, and the test results are shown in the attached figure. Figure 6 As shown in the figure, the initial discharge capacities of all experimental groups are similar, indicating that the electrode materials do not have difficulty in lithium ion deintercalation and severe polarization, which is consistent with the test results of the electrode resistance. After 50 cycles at 45°C, the discharge capacity decreased. The epoxy resin binder may have more reducing functional groups, which leads to electrochemical oxidation on the positive electrode and degradation, causing the discharge capacity of the battery active material to decrease rapidly. There is no significant difference with PVDF in the rest.
[0094] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A battery active material binder, characterized in that: It includes a high molecular homopolymer or copolymer, a conductive agent and a solvent; The mass percentage of the polymer homopolymer or copolymer in the solvent is 1%-20%, and the main structure of the polymer homopolymer or copolymer is one of polyurethane, polyurea, epoxy resin or polyimide; The solvent is at least one of NMP, DMAc, DMF, DAA and THF.
2. A battery active material binder according to claim 1, characterized in that : The mass percentage of the conductive agent in the solid component of the slurry is 1%-10%, and the conductive agent is at least one of Super PLi, conductive graphite and carbon nanotubes.
3. A method for preparing a polyurethane or polyurea adhesive, characterized in that : Includes the following steps: A1. Mix diisocyanate, monoanhydride, diamine, diol, monoamine, monoalcohol and solvent; A2, mixing at a temperature of 20-40°C for 1-3 hours; A3. Mix at a temperature of 60-120°C for 6-10 hours, with a solid content concentration of 1%-20% of chain polyurethane or polyurea material.
4. The preparation method according to claim 3, characterized in that : The molar ratio of the sum of the monoamine and the monoalcohol to the sum of the diamine, the diol and the diisocyanate is 2:n:(n+1), wherein n is 2-1000.
5. A method for preparing an epoxy resin adhesive, characterized in that : Includes the following steps: B1, mixing diglycidyl ether, monoglycidyl ether, diamine, dicarboxylic acid and solvent; B2, mixing at a temperature of 20-40°C for 1-3 hours; B3. A chain epoxy resin material having a solid content concentration of 1% to 20% is mixed at a temperature of 60-120°C for 6-10 hours.
6. The preparation method according to claim 5, characterized in that : The molar ratio of the monoglycidyl ether and diglycidyl ether to the diamine or dicarboxylic acid is 2:n:(n+1), wherein n is 2-1000.
7. A method for preparing a polyimide adhesive, characterized in that : Includes the following steps: C1, mixing tetracarboxylic dianhydride, monoanhydride, diamine and solvent; C2, mixing at a temperature of 20-40°C for 1-3 hours; C3. A chain polyimide material having a solid content concentration of 1% to 20% and mixed at a temperature of 60-150°C for 6-10 hours.
8. The method for preparing the polyimide adhesive according to claim 7, characterized in that : The molar ratio of the monoanhydride to the tetracarboxylic dianhydride and the diamine is 2:n:(n+1), wherein n is 2-1000; The monoacid anhydride is at least one selected from phthalic anhydride, hexahydrophthalic anhydride, maleic anhydride, tetrahydrophthalic anhydride, pentanedetracarboxylic dianhydride, methylmaleic anhydride and itaconic anhydride.
9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode active layer, wherein the positive electrode active layer contains a battery active material or a binder prepared by any one of claims 3 to 8; The current collector is at least one of copper foil, aluminum foil, composite copper foil and composite aluminum foil; The battery active material is a positive electrode active material, and the battery active material is at least one of lithium cobalt oxide, nickel-cobalt binary battery active material, nickel-manganese binary battery active material, nickel-cobalt-manganese ternary battery active material, lithium-rich battery active material and lithium iron phosphate.
10. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet according to claim 9.